2022
DOI: 10.1111/cas.15498
|View full text |Cite
|
Sign up to set email alerts
|

N4BP3 promotes angiogenesis in hepatocellular carcinoma by binding with KAT2B

Abstract: Hepatocellular carcinoma, as one of the most common malignant tumors of the digestive system, ranks sixth in the number of new cases and is the second leading cause of cancer-related deaths globally, with a high incidence rate and a high degree of malignancy. 1 Tumors in HCC are frequently associated with an abundance of new blood vessels, which play a critical role in tumor growth, invasion, and metastasis. 2 As a result, the majority of patients lose the opportunity for radical surgery when diagnosed. 3 Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Therefore, we hypothesize that KAT2B may regulate DNA damage repair through the acetylation of histones. Subsequently, we observed that H3K27ac decreased in expression after reducing KAT2B expression (Figure 6C,D), which is consistent with what others reported [41][42][43]. We also observed that the expression of BRCA2 was decreased in both KAT2B knockdown and KAT2B knockout cell lines (Figure 6C,D).…”
Section: Kat2b Affects Olaparib Sensitivity Through the Regulation Of...supporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, we hypothesize that KAT2B may regulate DNA damage repair through the acetylation of histones. Subsequently, we observed that H3K27ac decreased in expression after reducing KAT2B expression (Figure 6C,D), which is consistent with what others reported [41][42][43]. We also observed that the expression of BRCA2 was decreased in both KAT2B knockdown and KAT2B knockout cell lines (Figure 6C,D).…”
Section: Kat2b Affects Olaparib Sensitivity Through the Regulation Of...supporting
confidence: 90%
“…KAT2B, as a member of the BRD family, is a histone acetyltransferase and is associated with homologous recombination repair [27][28][29][30][31]. Previous reports from other laboratories have demonstrated that the acetylation induced by KAT2B significantly modulates the function of H3K27 [41][42][43]. Our present study now adds to this knowledge and shows that KAT2B knockdown and knockout affect the acetylation of H3K27 and the expression of BRCA2 (Figure 6C,D).…”
Section: Discussionsupporting
confidence: 77%
“…Hexu Han et al found that NEDD4 binding protein 3 (N4BP3) was highly expressed in HCC, and the C-terminus of N4BP3 interacted with lysine acetyltransferase 2B (KAT2B) to regulate the distribution of the promoter of acetyl-histone H3 (Lys 27) (H3K27 ac) and increase the expression of the signal transducer and activator of transcription 3 (STAT3), thereby increasing the expression and secretion of vascular endothelial growth factor A (VEGFA) to promote angiogenesis in HCC. Furthermore, the efficacy of sorafenib was enhanced, providing a new theoretical basis for the selection of therapeutic targets in HCC [143]. Nonetheless, the exact roles of NEDD 4 and NEDD4L in HCC need to be further investigated to guide future drug research directions and identify effective diagnostic and prognostic markers for HCC to improve patients' survival (Figure 5) (Table 1).…”
Section: Nedd4/neddl and Liver Diseases 221 Nedd4/neddl And Liver Cancermentioning
confidence: 99%
“…Cellular extracts were meticulously prepared and subsequently analyzed through the western blotting, using appropriate antibodies, as detailed in the reference methodologies [16]. The primary antibodies used in our study included: anti-NAT10 (1:1000, 13365-1-AP, Proteintech, Wuhan, China), anti-RelA/p65 (1:1000, 8242, CST, Boston, MA, USA), anti-Flag-tag (F1804, Sigma, St. Louis, MO, USA), anti-IKba (1:1000, 4814, CST, Boston, MA, USA), anti-phospho IKba (Ser32/36) (1:1000, 9426, CST, Boston, MA, USA), anti-NF-κB p65 (Ser536) (1:1000, 3033, CST, Boston, MA, USA), anti-IKKB (1:1000, 15649-1-AP, Proteintech, Wuhan, China), anti-IKK-alpha (1:1000, GB11923, ServiceBio, Wuhan, China), and anti-β-actin (1:10,000, 66009-1-AP, Proteintech, Wuhan, China).…”
Section: Western Blotting Assaymentioning
confidence: 99%
“…Previous studies have suggested a significant involvement of the NF-κB signaling pathway in lung cancer progression [16,17]. Exploring NAT10's influence on the activation of the NF-κB signaling pathway, we used Dualluciferase reporter gene assays on our previously established stable cell lines.…”
Section: Nat10 Promotes Lung Cancer Through the Activation Of Nf-κb S...mentioning
confidence: 99%